Assessing micro-finance services in agricultural sector development: a case study of semi-formal financial institutions in Tanzania - Rweyemamu, D.C.; Kimaro, M.P.; Urassa, O.M. (International Food Policy Research Institute, 2004)
A Case Study of Semi-Formal Financial Institutions in Tanzania Background In Tanzania, as in other parts of Africa, lack of credit severely constrains sustainable agricultural development. Deficient or inappropriate collateral, credit rationing, lender preferences for high-income customers borrowing large amounts, and bureaucratic procedures in the formal financial sector are often identified as key factors contributing to low access to credit among most rural dwellers.